Virtually There: a Process of Collaboration - Reid, Bryonie (Irish Journal of Arts Management and Cultural Policy, 2020)
This paper introduces action research on Virtually There, a long-running project placing artists in schools through the interactive whiteboard and in close collaboration with teachers. It considers questions of organisational and relational structure, the operation of the project through time and process, and the meaning of success in this context.